Determination of antibiotics in bean sprouts by UHPLC-MS/ MS-internal standard method - ZHANG Xiaoyi; ZHENG Sanyan; ZHANG Xiuyao; LI Ruifen; YANG Shuran (Shanghai yufang yixue)
ObjectiveTo establish an ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS)-internal standard method for the simultaneous determination of 59 antibiotics, including quinolones, sulfonamides, tetracyclines, macrolides and nitroimidazole in bean sprouts.MethodsThe internal standard compounds and 5.0 mL of acetonitrile containing 0.1% formic acid were added into 5.0 g of the sample, and then extracted by ultrasonication. The extracted supernatant was filtered by 0.22 µm membrane and then injected into 1.0 µL of the sample directly. Methanol containing 0.1% formic acid and 2.0 mmol·L-1 ammonium formate containing 0.1% formic acid were taken as the mobile phases to conduct gradient elution. The separation was achieved on an ACQUITY PREMIER BEH C18 column. The separated analytes were detected by the electrospray ionization (ESI) in multiple reaction monitoring (MRM) mode, and quantified by internal standard method.ResultsThe 59 kinds of antibiotics in bean sprouts had a good linear relationship in the range of 10 μg·kg-1 to 1 000 μg·kg-1. The limits of detection (LODs) and the limits of quantification (LOQs) of the method for soybean sprouts ranged from 0.1 μg·kg-1 to 3.0 μg·kg-1 and 0.4 μg·kg-1 to 10.0 μg·kg-1, respectively. While, the LODs and LOQs of the method for mung bean sprouts ranged from 0.1 μg·kg-1 to 2.0 μg·kg-1 and 0.4 μg·kg-1 to 7.0 μg·kg-1, respectively. The average recoveries of the 59 kinds of antibiotics at four levels (10、50、200、800 μg·kg-1) in soybean sprouts were 82.1%‒122.3%, with the relative standard deviations (RSDs) of 1.2%‒15.4% (n=6). However, the average recoveries of the 59 kinds of antibiotics in mung bean sprouts were 87.3%‒119.1%, with the RSDs of 0.9%‒15.0% (n=6).ConclusionThe method is rapid, highly sensitive and accurate, which can be used for rapid screening of quinolones, sulfonamides, tetracyclines, macrolides, and nitroimidazole antibiotics in large quantities of bean sprouts.